Do fetuses move their lips to the sound that they hear? An observational feasibility study on auditory stimulation in the womb. Issue 1 (December 2016) - Reissland, Nadja; Francis, Brian; Buttanshaw, Louisa; Austen, Joe; Reid, Vincent
Abstract Background We investigate in this feasibility study whether specific lip movements increase prenatally when hearing a particular sound. We hypothesised that fetuses would produce more mouth movements resembling those required to make the sound stimulus they heard (i.e. mouth stretch) compared with a no-sound control group who heard no specific auditory stimuli. Secondly, we predicted that fetuses hearing the sound would produce a similar number of mouth movements unrelated to the sound heard (i.e. lip pucker) as the no-sound group of fetuses. Methods In an observational feasibility study, 17 fetuses were scanned twice at 32 and 36 weeks of gestation, and two different types of mouth movements were recorded. Three fetuses received an auditory stimulus, and 14 did not. A generalised mixed effects log-linear model was used to determine statistical significance. Results Fetuses in the sound group performed one specific mouth movement (mouth stretch) significantly more frequently than fetuses in the no-sound group. A significant interaction between group and gestational age indicates that there was differential change in this specific movement as age increases (X 2  = 7.58 on 1 df, p  = 0.006), with the no-sound group showing a decline of 76 % between 32 weeks and 36 weeks (p  < 0.001), whereas the sound group showed no significant change over time (p  = 0.41). There was no significant difference between the sound group and no-sound group in the frequency of lip puckering—the second, unrelated mouth movement (p  = 0.35). Conclusions These results suggest that a sound stimulus is associated with an increase in specific, rather than general, mouth movements. The results are informative for the development of infant speech and potentially could also lead to a diagnostic test for deafness in utero. More research is needed to replicate this research with a randomised design and with a range of different auditory stimuli which would be produced with different mouth movements, such as "o" which would be seen as pursed lips.